Metallothionein isoform 3 and proximal tubule vectorial active transport - Kim, Doyeob; Garrett, Scott H.; Sens, Mary Ann; Somji, Seema; Sens, Donald A. (Kidney international, 2002)
Metallothionein isoform 3 and proximal tubule vectorial active transport. Metallothionein isoform 3 (MT-3) is expressed in the proximal tubule cells of the human kidney. The goal of the present study was to further characterize the basal expression of MT-3 in the proximal tubule and to determine if MT-3 participates in the maintenance of proximal tubule cell function. Expression of MT-3 mRNA was determined in the intact proximal tubule using microdissection and reverse transcription-polymerase chain reaction (RT-PCR). Basal expression of MT-3 mRNA and protein was determined in cultured human proximal tubule (HPT) cells and an immortalized proximal tubular cell line, HK-2 cells, using RT-PCR and immunoblotting. The MT-3 gene was stably transfected into the HK-2 cell line using the pcDNA3.1/Hygro (+) vector. MT-3 mRNA was detected in the proximal tubule of the in situ kidney with relative expression in excess to that of the β-actin housekeeping gene. The mortal HPT cells were shown to express both MT-3 mRNA and protein and to form domes, while immortal HK-2 cells were shown to have no expression of MT-3 mRNA and protein nor to form domes. The stable transfection of MT-3 in HK-2 restored MT-3 expression and dome formation to the HK-2 cells. MT-3 mRNA is present in the human proximal tubule, and MT-3 expression is involved in the transport function of a human renal cell line that retains properties of the proximal tubule.